Pediatric running injuries - Seto, C. K.; Statuta, S. M.; Solari, I. L. (Clinics in Sports Medicine, 2010)
As more children have become involved in athletic activities and running, there has been a significant increase in overuse injuries. The young athlete with open growth plates is vulnerable to unique overuse injuries involving the apophyses, articular cartilage, and growth plate. The physician caring for these young athletes needs to be aware of these conditions to diagnose and treat them appropriately. Physicians should also be aware of the risk of overtraining and overuse injury in athletes participating in year-round sports and competition. Current guidelines for overuse injury prevention in young athletes are primarily based on consensus and expert opinion. Further research is needed to provide evidence-based guidelines for overuse injury prevention in young athletes and runners.